The biomechanical analysis of the taekwondo front-leg axe-kick - Tsai, Y. J.; Gu, G. H.; Lee, C. J.; Huang, C. F.; Tsai, C. L. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of the study was to analyze the biomechanics of taekwondo front-leg axe-kick. One force plates, two synchronized high-speed cameras were used to measure biomechanical parameters in each phase of the front-leg axe-kick. The results included: 1. The average reaction time and movement time were 0.423 s and 0.327 s, which respectively occupied about 56% and 44% of attack time. 2. The maximum velocity of hip, knee and ankle were 1.74 m/s, 5.25 m/s and 7.43 m/s respectively. When the kicking leg touched the target, the velocity of knee and ankle were 0.78m/s, 1.72m/s, and 4.64m/s respectively. 3. The peak vertical GRF and impulse were 0.96 BW and 77.57N-S. For decreasing the movement time, it's suggested that an athlete should increase the power and flexibility of lower extremities during the training section.